50 kHz bottom backscattering measurements from two types of artificially roughened sandy bottoms. (15th June 2016) - Son, Su-Uk; Cho, Sungho; Choi, Jee Woong
Abstract: Laboratory measurements of 50 kHz bottom backscattering strengths as a function of grazing angle were performed on the sandy bottom of a water tank; two types of bottom roughnesses, a relatively smooth interface and a rough interface, were created on the bottom surface. The roughness profiles of the two interface types were measured directly using an ultrasound arrival time difference of 5 MHz and then were Fourier transformed to obtain the roughness power spectra. The measured backscattering strengths increased from −29 to 0 dB with increasing grazing angle from 35 to 86°, which were compared to theoretical backscattering model predictions. The comparison results implied that bottom roughness is a key factor in accurately predicting bottom scattering for a sandy bottom.